PENERAPAN METODE LEAN SIX SIGMA UNTUK MENINGKATKAN KINERJA OPERASI DALAM PENANGANAN BONGKAR MUAT PETIKEMAS DOMESTIK DI TERMINAL BERLIAN PELABUHAN TANJUNG PERAK SURABAYA - Handryan Erwan Ering; Suparno Suparno (Politeknik Negeri Lhokseumawe, 2021)
Abstract: The aims of this research to analyze the condition of container loading and unloading services at Terminal Berlian, find out the factors that cause low operating performance, as well as design solutions to improve operating performance in Terminal Berlian using the lean six sigma method. This research uses an exploratory qualitative approach which explains why it is questioned and discusses what was produced by interviews with 15 informants who determined structural officials who were experienced in the Operations Directorate and supported other data sourced from operational reports. The results of the analysis show the root of the dominant problem in the work process are waiting for the departure process, waiting for the truck losing cargo, waiting for the load from CY, unloading idle time and trouble of the equipment. The design of improvement is carried out by strategies to reduce waste by eliminating NVA NOT work preparation and departure of the ships, eliminating NVA waiting times, and reducing NOT breaks, and the strategies to improve process capability by increasing the speed of cycle time and increase using HMC per vessel. The results of the research shows that the application of the lean six sigma method can improve the operating performance of Terminal Berlian with an average increase in cycle time of 39.11% and an average increase in the ratio of ET: BT to 39.96%.Keyword: Lean Six Sigma, DMAIC, Value Stream Mapping, Cause Effect Diagram